Drainage, antibiotics and teamwork: overcoming al liver abscess in pediatrics (Archives of Pediatrics of Uruguay, 2025)
Introduction: hepatic abscesses in pediatrics can be of pyogenic or amoebic origin, and timely management is a crucial pillar for better clinical outcomes.Case Description: we present the case of an 8-year-old male patient from San Marcos, Sucre, who was admitted with fever, pain in the right hypochondrium, and hepatomegaly. Imaging revealed a hypoechoic lesion in the liver, leading to a diagnosis of pyogenic vs. amoebic hepatic abscess. Treatment with ceftriaxone and metronidazole was initiated, and drainage was performed due to complications: pleural effusion.Hepatic abscess in children represents a diagnostic and therapeutic challenge. In this case, the combination of advanced imaging and a multidisciplinary approach was key to establishing a precise and early diagnosis. The decision to initiate appropriate empirical antibiotic treatment and timely surgical intervention allowed for effective management of complications, such as pleural effusion. This case highlights the need for a collaborative approach among pediatricians, infectologists, gastroenterologists, and surgeons to optimize treatment and improve prognosis in pediatric patients with hepatic abscesses.Conclusions: the patient evolved favorably and was discharged after 14 days of hospitalization. This case underscores the importance of a comprehensive approach in the treatment of hepatic abscesses in children.
Keywords: Liver Abscess; Pediatrics